2000
DOI: 10.1016/s0002-9440(10)64814-6
|View full text |Cite
|
Sign up to set email alerts
|

p63 Is a Prostate Basal Cell Marker and Is Required for Prostate Development

Abstract: The p53 homologue p63 encodes for different isotypes able to either transactivate p53 reporter genes (TAp63) or act as p53-dominant-negatives (DeltaNp63). p63 is expressed in the basal cells of many epithelial organs and its germline inactivation in the mouse results in agenesis of organs such as skin appendages and the breast. Here, we show that prostate basal cells, but not secretory or neuroendocrine cells, express p63. In addition, prostate basal cells in culture predominantly express the DeltaNp63alpha is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
437
1
15

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(483 citation statements)
references
References 25 publications
30
437
1
15
Order By: Relevance
“…Owing to the predominant mRNA expression of DN isoforms rather than TA isoforms in normal urothelial cells and low-grade urothelial tumour cells, our results suggest that DNp63a is the predominant isoform in these cell lines. These results are consistent with published data in human keratinocytes (Yang et al, 1998) and human prostate basal cells (Signoretti et al, 2000).…”
Section: Expression Of P63 In Cultured Human Normal and Neoplastic Ursupporting
confidence: 94%
See 1 more Smart Citation
“…Owing to the predominant mRNA expression of DN isoforms rather than TA isoforms in normal urothelial cells and low-grade urothelial tumour cells, our results suggest that DNp63a is the predominant isoform in these cell lines. These results are consistent with published data in human keratinocytes (Yang et al, 1998) and human prostate basal cells (Signoretti et al, 2000).…”
Section: Expression Of P63 In Cultured Human Normal and Neoplastic Ursupporting
confidence: 94%
“…In negative controls, the primary antibody was substituted for nonimmune mouse sera. Nonneoplastic prostate glands were used as positive controls (Signoretti et al, 2000). The slides were independently reviewed by two of the authors (KF and KS) who were blinded to the clinicopathologic data.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The truncated forms are thought to inhibit cell cycle arrest and apoptosis driven by transactivating p63/p53 interaction. 12 The truncated isoforms are preferentially expressed in the basal cell compartment of normal epithelium 12,13 and transactivating forms are more widely distributed in benign and neoplastic epithelium. 14 Consequently, different isoforms of p63 appear to play a role in maintaining the epithelial stem cell population, spurring epithelial differentiation and inducing neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Previous studies in several laboratories have shown p63 expression in many normal tissues including squamous epithelia, urothelium, bronchial epithelium, and the myoepithelial layers of breast, prostate and submucosal glands. [9][10][11][12] Expression has also been established in a variety of neoplasms, including squamous, urothelial, endometrial, and papillary thyroid carcinomas and thymomas. [13][14][15][16][17][18][19][20] p63 expression in salivary gland and salivary neoplasms has also been investigated.…”
mentioning
confidence: 99%